Modifications in magnetic anisotropy of M-type strontium hexaferrite crystals by swift heavy ion irradiation - Kaur, Balwinder; Bhat, Monita; Licci, F.; Kumar, Ravi; Kulkarni, S. D.; Joy, Pattayil Alias; Bamzai, K. K.; Kotru, P. N. (Journal of Magnetism and Magnetic Materials, 2006)
Using vibrating sample magnetometery (VSM) 50 MeV Li(3+) ion irradiation effects on magnetic properties of single crystals of SrGa(x)In(y)Fe(12-(x+y))O(19) (where x = 0, 5, 7, 9; y = 0, 0.8, 1.3, 1.0), are reported. The substitution of Ga and In in strontium hexaferrite crystals decreases the value of magnetization sharply, which is attributed to shifting of collinear magnetic order to a non-collinear one. Reduction of magnetization is also explained to be as a result of the occupation of the crystallographic sites of Fe(3+) by Ga(3+) and In(3+). The Li(3+) ion irradiation decreases the value of magnetization, irrespective of whether the crystals are Ga-In substituted or unsubstituted crystals of SrFe(12)O(19). The result is interpreted in terms of the occurrence of a paramagnetic doublet in crystals replacing magnetic sextuplet as a result of irradiation. Substitution of Ga-In in Strontium hexaferrite decreases the value of anisotropy constant. Irradiation with Li(3+) ions increases the values of anisotropy field for both substituted as well as unsubstituted crystals. Substitution with Ga-In also decreases the Curie temperature (T(c)) but the irradiation with Li(3+) ions does not affect the curie temperature of either Ga-In substituted or pure SrFe(12)O(19) crystals. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: anisotropy field; Curie temperature; irradiation; Magnetic anisotropy; Magnetization

Microwave dielectric and attenuation properties of Ni0.7-xCoxZn0.3Fe2O4 thick films - Rendale, M. K.; Kulkarni, S. D.; Puri, Vijaya (Microelectronics International, 2009)
Purpose - The aim of this paper is to investigate permittivity of nano structured Ni0.7-xCoxZn0.3Fe2O4 thick films at microwave frequencies. Design/methodology/approach - Nanosized Ni0.7-xCoxZn0.3Fe2O4 ferrites with x = 0, 0.04, 0.08 and 0.12 were prepared by sucrose precursor technique using the constituent metal nitrates. Thick films of the ferrites were fabricated on alumina substrates by screen-printing technique. Microwave dielectric constant (epsilon') and the loss factor (epsilon `') for the thick films were measured by VSWR slotted section method in the 8-18 GHz range of frequencies. Microwave attenuation properties were studied using a waveguide reflectometer set up. Findings - Both the epsilon' and epsilon `' were found to vary with frequency and composition x It is observed that, value of epsilon' increases with increase in x, due to the increase in bulk density and reduction in porosity of the material, that resulted due to the substitution of cobalt in Ni-Zn ferrite. The microwave transmission loss offered by the thick films was found to increase with the increase in cobalt concentration x Within the band width of 4 GHz (from 12-16 GHz), all the films except that with x = 0.04 offered the reflection loss of less than 3 dB. Originality/value - The dielectric constant of Ni0.7-xCoxZn0.3Fe2O4 thick films have been reported for the first time. These thick films provide scope for cost effective planar ferrite devices.
Keywords: Microwaves; Oxides; Thick-film circuits